# Lucas polynomials

The polynomials $V_n(x)$ (cf. [BeHo] and [Lu]) given by \left.\begin{align}V_0(x) &= 2,\\ V_1(x) &= x,\\ V_n(x) &= x V_{n-1}(x)+V_{n-2}(x),\quad n = 2,3,\dots \end{align}\quad\right\}\tag{a1} They reduce to the Lucas numbers $L_n$ for $x=1$, and they satisfy several identities, which may be easily proved by induction, e.g.: \begin{alignat}{1} &V_{-n}(x) &=\ & (-1)^nV_n(x);\tag{a2}\\ &V_{m+n}(x) &=& V_m(x)V_n(x) - (-1)^nV_{m-n}(x);\tag{a3}\\ &V_{2n}(x) &=& V_n^{\;2}(x)-2(-1)^n;\tag{a4}\\ &V_{2n+1}(x)\ &=& V_{n+1}(x)V_n(x)-(-1)^nx;\tag{a5}\\ &U_{2n}(x) &=& U_n(x)V_n(x),\tag{a6} \end{alignat} where $U_m(x)$ denote the Fibonacci polynomials; $$V_n(x) = \alpha^n(x)+\beta^n(x),\tag{a7}$$ where $$\alpha(x) = \frac{x+(x^2+4)^{1/2}}{2},\quad \beta(x) = \frac{x-(x^2+4)^{1/2}}{2},$$ so that $\alpha(x)\beta(x) = -1$; and $$V_n(x) = \sum_{j=0}^{[n/2]} \frac{n}{n-j}\; \frac{(n-j)!}{j!(n-2j)!}\; x^{n-2j},\quad n=1,2,\dots,\tag{a8}$$ where $[y]$ denotes the greatest integer in $y$.
The Lucas polynomials are related to the Chebyshev polynomials $T_n(x) = \cos(n\theta)$, $\cos(\theta) = x$, by $$V_n(x) = 2i^{-n} T_n\Big(\frac{ix}{2}\Big),\; i = (-1)^{1/2}.\tag{a9}$$ J. Riordan [Ri] considered the polynomials $h_n(x) = i^{-n}V_n(ix)$ and the Lucas-type polynomials $$L_n(x) = \sum_{j=0}^{[n/2]} \frac{n}{n-j}\; \frac{(n-j)!}{j!(n-2j)!}\; x^{n-j} = x^{n/2}V_n(x^{1/2}),\; n = 1,2,\dots,\tag{a10}$$ in a derivation of Chebyshev-type pairs of inverse relations. V.E. Hoggatt Jr. and M. Bicknell [HoBi] found the roots of $V_n(x)$. These are $x_j = 2i\cos((2j+1)\pi/2n)$, $j=1,\dots,n-1$. Bicknell [Bi] showed that $V_m(x)$ divides $V_n(x)$ if and only if $n$ is an odd multiple of $m$. G.E. Bergum and Hoggatt Jr. introduced in [BeHo] the bivariate Lucas polynomials $V_n(x,y)$ by the recursion \begin{equation} \left.\begin{align}V_0(x,y) &= 2,\\ V_1(x,y) &= x,\\ V_n(x,y) &= x V_{n-1}(x,y)+ y V_{n-2}(x,y),\quad n = 2,3,\dots \end{align}\right\}\end{equation}\tag{a11} generalized (a7) for $V_n(x,y)$, and showed that the $V_n(x,y)$ are irreducible polynomials over the rational numbers if and only if $n=2^k$ for some positive integer (cf. also Irreducible polynomial). The formula $$V_n(x,y) = \sum_{j=0}^{[n/2]} \frac{n}{n-j}\; \frac{(n-j)!}{j!(n-2j)!} \; x^{n-2j}y^j,\; n = 1,2,\dots,\tag{a12}$$ which may be derived by induction on $n$ or by expanding the generating function of $V_n(x,y)$, generalizes (a8).
Ch.A. Charalambides [Ch] introduced and studied the Lucas and Lucas-type polynomials of order $k$, $V_n^{\;(k)}(x)$ and $L_n^{\;(k)}(x)$. The Lucas-type polynomials of order $k$ satisfy the recurrence \left.\begin{alignat}{1}L_1^{\;(k)}(x) &= x,\\ L_n^{\;(k)}(x) &= x\Big(n+\sum_{j=1}^{n-1}L_{n-j}^{\;(k)}(x)\Big),\; & n = 2,\dots,k, \\ L_n^{\;(k)}(x) &= x\sum_{j=1}^k L_{n-j}^{\;(k)}(x),\; & n = k+1,k+2,\dots \end{alignat}\right\}\tag{a13} These polynomials have the binomial and multinomial expansions \begin{alignat}{1}L_n^{\;(k)}(x) &= -1 + \sum_{j=0}^{[n/(k+1)]}(-1)^j\frac{n}{n-jk}\;\frac{(n-jk)!}{j!(n-jk-j)!}x^j(1+x)^{n-jk-j}\\ &=\sum \frac{n_1+2n_2+\cdots+kn_k}{n_1+\cdots+n_k}\;\frac{(n_1+\cdots+n_k)!}{n_1!\cdots n_k!} x^{n_1+\cdots+n_k},\end{alignat}\tag{a14} where the second summation is taken over all non-negative integers $n_1,\dots,n_k$ such that $n_1+2n_2+\cdots +kn_k = n$, and they are related to the Fibonacci-type polynomials of order $k$ (cf. [Ph] and [PhGePh2] and Fibonacci polynomials), $F_n^{\;(k)}(x)$, by $$L_n^{\;(k)}(x) = x \sum_{j=1}^{\min\{n,k\}} jF_{n-j+1}^{\;(k)}(x).\tag{a15}$$ Furthermore, \begin{align}V_n^{\;(k)}(x) &= x^{-n} L_n^{\;(k)}(x^k)\\ &= \sum_{j=1}^{\min\{n,k\}} jx^{k-j+1}U_{n-j+1}^{\;(k)}(x),\; n=1,2,\dots,\; k=2,3,\dots,\end{align}\tag{a16} where the $U_n^{\;(k)}(x)$ are the Fibonacci polynomials of order $k$ (cf. [PhGePh]). Charalambides [Ch] showed that the reliability of a circular consecutive $k$-out-of-$n$: $F$-system, $R_c(p; k,n)$, whose components function independently with probability $p$ (and $q = 1-p$) is given by \begin{align}R_c(p; k,n) &= q^n L_n^{\;(k)}\Big(\frac{p}{q}\Big)\\ &= -q^n + \sum_{j=0}^{[n/(k+1)]}(-1)^j\frac{n}{n-jk}\; \frac{(n-jk)!}{j!(n-jk-j)!}p^jq^{jk}.\end{align}\tag{a17}